1990
DOI: 10.1128/jvi.64.2.957-961.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cationic liposomes (Lipofectin) mediate retroviral infection in the absence of specific receptors

Abstract: We have used cationic liposomes (Lipofectin) to facilitate retrovirus infection of cells lacking the homologous viral receptor. Ecotropic murine leukemia virus and packaged retroviral vectors were shown to infect mink cells, and amphotropic packaged retroviral vectors were shown to infect hamster cells in the presence of Lipofectin but not in the presence of Polybrene. Lipofectin-mediated infection of cells lacking the homologous receptor results in a titer approximately 0.1% of the titer in cells with the hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…1A, lanes 1 and 7, respectively), indicating that virions could launch RNA replication if they were delivered directly to the cytoplasm, bypassing receptor-mediated entry. Similar results have been obtained by using cationic lipids, including Lipofectin, to deliver retroviruses (8,17) and hepatitis delta virus (5) to nonpermissive cells. Longer exposure of the autoradiograph indicated that NOV could infect BHK cells, albeit at a very low efficiency (Fig.…”
supporting
confidence: 71%
“…1A, lanes 1 and 7, respectively), indicating that virions could launch RNA replication if they were delivered directly to the cytoplasm, bypassing receptor-mediated entry. Similar results have been obtained by using cationic lipids, including Lipofectin, to deliver retroviruses (8,17) and hepatitis delta virus (5) to nonpermissive cells. Longer exposure of the autoradiograph indicated that NOV could infect BHK cells, albeit at a very low efficiency (Fig.…”
supporting
confidence: 71%
“…The starting point of this study was to characterise envelope‐independent transduction, previously observed when investigating the use of cationic liposomes to enhance retroviral transduction rates 11. An important aspect of this work is the analysis of transduction kinetics rather than simply looking at a fixed (and distant) timepoint after exposure of the cells, in contrast to earlier reports of envelope‐independent delivery 9, 10. In summary, maximal initial rates of transduction with non‐enveloped virus were obtained by pre‐incubation for 30 min with a 10‐µg dose of DOTAP, whereas maximal envelope mediated infectivity of MLV‐A required 2.5 µg DC‐Chol/DOPE 11.…”
Section: Discussionmentioning
confidence: 99%
“…Gag‐pol expression in the presence of a suitable packagable RNA enables the production of particles identical in structure and density to infectious virus 9, with the exception that they lack any specific viral envelope proteins and so are non‐infectious. Nevertheless, infectivity can be obtained in certain situations when another means of inducing membrane fusion is provided, such as by cationic liposomes 9–11 or the fusogenic envelope protein of vesicular stomatitis virus 12. Co‐expression of a retroviral envelope protein leads to its efficient incorporation in the lipid membrane of the gag‐based particle 13.…”
Section: Introductionmentioning
confidence: 99%
“…Innes and coworkers demonstrated infection with amphotropic retroviruses of Chinese hamster ovary cells in the presence of lipofectin. Lipofectin-mediated infection of cells lacking the receptor resulted in a titer of approximately 0.1% of the titer in cells which contained the homologous receptor [81]. Adams et al demonstrated infection in HeLa cells when replication defective adenovirus and ecotropic retrovirus were simultaneously added to the cells [82].…”
Section: Expression Of Retroviral Receptorsmentioning
confidence: 99%